Analysis and verification of stresses in reinforced concrete bridge projects of the box type with sequential application of prestress based on the successive advancement method (Research, Society and Development, 2024)
Given the importance of road bridge systems for the development of a country, rigor in the design process becomes extremely essential in order to meet all requirements related to their functionality. One of the challenging aspects of avoiding possible collapse problems at the beginning or during the construction phase of the project is the selection of the construction process. In this context, the criteria for defining the construction process to be adopted is intrinsically linked to cost, ease of execution, and safety during the creation of the work of art, construction time and the technical capacity of the construction professionals. In this study, deformation analyses and the evolution of efforts in the upper fibers of a bridge were carried out based on conventional construction methods, taking into account the application of pre-stress during construction, aiming to compare the results. Highlighting that the critical tensions were overcome with the help of applying pre-stress in a phased and/or sequential manner. The structural system in question is a single-cell box bridge made of pre-stressed concrete with variable height, measuring 2.50 m in the middle of the span and 4.70 m at the supports. The computational numerical modelling was developed based on the use of finite element programs CSiBridge v.20 and Robot Structural, considering bar and plate/shell/shell elements. Using the method of successive symmetric advances, a longitudinal, linear-static analysis was carried out (neglecting dynamic effects), taking into account the zero, corresponding and closing staves with length measurements of 6.40 m, 4.20 m and 3.00 m, respectively. The results were compared, where it was concluded that the efforts obtained in the construction phase after closing the consoles turned out to be relatively lower due to the redistribution of efforts, taking into account the change in the structural system from isostatic to hyperstatic. With this change, tensile stresses appeared in the lower fibers (this during the construction phase), increasing by 92.10% during the operation phase. The tensile efforts of the upper fibers in the support area increased by 85.6% from the construction phase to the operation phase. Regarding the pre-stressing strength of the concrete, it was applied in order to guarantee reduced losses resulting in values lower than 15%.